'And wouldst thou wrong thy only child?': The Crisis of Affective Kinship in Coleridge's 'Christabel'. Issue 1 (April 2018) - Mitsein, Rebekah
Abstract : Despite the tendency for scholars to read Samuel Taylor Coleridge's 'Christabel' as an unfinished poem, I argue that analysing the 'Conclusion to Part II' as the ending, so to speak, dramatises the tensions that accompanied evolving notions of the late eighteenth-century and early nineteenth-century British family. As consanguineous, patriarchal models of kinship began to be replaced by a more sentimental understanding of family, social and political writers increasingly espoused the theory that other kinds of social relationships could or should emulate affective kinship. Though Coleridge himself seems to have embraced this philosophy at one point, I argue that the 'Conclusion to Part II' brings kinship to the fore of 'Christabel' in a way that problematised these contemporary theories about families, both as systems in and of themselves and as the perceived building blocks of society. It does so, in part, by evoking Gothic portrayals of affective kinship from other literature of the time and then importing the anxieties of the Gothic into the domestic sphere.